Analysis Of Carbohydrates Role In The Performance Of Soccer Athletes: Systematic Literature Review - Muhammad Nailul Ajilla'; Bambang Priyono (Universitas Negeri Semarang, 2025)
The purpose of this study was to analyze the role of carbohydrates in the performance of soccer athletes. A Systematic Literature Review (SLR) was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The literature search, conducted across databases using specific keywords, identified 152 articles published between 2020 and 2024. After applying the inclusion and exclusion criteria, 42 relevant articles were selected, while 110 were excluded due to inaccessibility or irrelevance. Further screening based on keywords related to soccer, carbohydrates, and performance resulted in 27 articles, of which 10 were considered the most relevant for analysis. The study concluded that proper nutrition, especially carbohydrate intake, plays a vital role in maintaining energy levels, improving endurance, and supporting overall physical and cognitive performance. Carbohydrates contribute to better metabolism, delay fatigue, and support mental functions that are essential for decision-making during matches. This study emphasizes the importance of adhering to science-based nutritional guidelines and consulting with an experienced sports nutritionist to help athletes optimize performance and maintain health during training and competition.